A Comparison Of The Effect Of Three Glide Path Techniques On The Centrality Of Curved Root Canals Prepared With ProTaper Next (In Vitro Study) (Journal of Hama University, 2019)
Background and Aim: Some complications may occur as a change in the canal path and apical transportation during the preparation of the curved root canals. The process of securing a glide path has a good effect in alleviating these complications. Hence, the aim of study was to assess the ability of three glide path techniques: K-Files Manual - ProGlider - PathFile in terms of maintaining the centrality of curved root canals prepared with ProTaper Next.Materials and Methods:40 canals from upper and lower molars with a curvature ranging from 25 to 45 degrees were divided randomly into 4 groups, each group achieved a glide path with one of the systems mentioned above, while the fourth group remained without any glide path achievement, then canals of all groups were prepared using the ProTaper Next system. Radial images were taken before and after preparation, analyzed them in AutoCAD version 2018, data recording and statistical analysis by SPSS version 25.Results: The four groups maintained the center ratio of the canal in the same amount at the three points assigned along the canal without recording any statistically significant differences.Conclusions: None of the glide path systems used in this study could fully maintain the centrality of the canal. The three glide path systems used had the same ability to maintain centralization without any obvious differences.